Intentions to participate in adolescent training programs: Evidence from Uganda - Bandiera, Oriana; Goldstein, Markus; Rasul, Imran; Burgess, Robin; Gulesci, Selim; Sulaiman, Munshi (Oxford Academic, 2022)
This article was published in The Journal of the European Economic Association [© 2010 by the European Economic Association] and the definite version is available at: https://doi.org/10.1111/j.1542-4774.2010.tb00525.x The Article's website is at: https://academic.oup.com/jeea/article-abstract/8/2-3/548/2296034